2021
DOI: 10.1039/d1ra01962g
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical synthesis of hydroxyl group-functionalized PProDOT/ZnO for an ultraviolet photodetector

Abstract: Ultraviolet (UV) detectors based on zinc oxide (ZnO) nanorods (NRs) are ideal materials for UV radiation detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Figure a is a comparison of the XRD curves of the two PDs, where (002) and (004) correspond to the characteristic peaks of ZnO. It can be observed that the sharp peak (002) of the PDs corresponding to the C -axis orientation of ZnO is reduced to a certain extent after spin-coating P3HT:PC61BM, which is because the coverage of P3HT:PC61BM blocks a part of ZnO . Since the peak positions of the P3HT:PC61BM/ZnO NWs PD and the ZnO NWs PD are basically consistent, the P3HT:PC61BM/ZnO NWs PD was further subjected to XPS test to analyze the presence and composition of components.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure a is a comparison of the XRD curves of the two PDs, where (002) and (004) correspond to the characteristic peaks of ZnO. It can be observed that the sharp peak (002) of the PDs corresponding to the C -axis orientation of ZnO is reduced to a certain extent after spin-coating P3HT:PC61BM, which is because the coverage of P3HT:PC61BM blocks a part of ZnO . Since the peak positions of the P3HT:PC61BM/ZnO NWs PD and the ZnO NWs PD are basically consistent, the P3HT:PC61BM/ZnO NWs PD was further subjected to XPS test to analyze the presence and composition of components.…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen that, in addition to the obvious UV absorption edge corresponding to ZnO, after spin coating, the PD has an obvious steep absorption edge corresponding to P3HT:PC61BM. Due to the strong interaction between the chains of organics, there are two shoulder peaks in the middle of 500–600 nm, which leads to more light absorption and efficient charge transport …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations